The Relationship of Emotional Level with the Menstrual Cycle in Adolescent Women - Yuni Handayani; Rizki Fitrianingtyas; Yuningsih Yuningsih; Kustin Kustin (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
Emotions are related to emotional expression or profound changes that accompany emotions, characterizing individuals who are easily aroused to display emotional behavior. The factors that affect the menstrual cycle are estrogen production, nutritional status, stress factors, regular exercise, emotional changes, smoking and taking drugs. Emotional changes due to a stressor have been associated with hormonal fluctuations during the menstrual cycle. Menstrual cycle is a menstrual cycle that women experience every month starting from the first day of menstruation. In a disturbed psychological state, activation of the limbic system occurs. The menstrual cycle varies, mostly 90% of women have a cycle of 25-35 days and only 10-15% have a cycle length of 28 days. The design of this study uses a correlation with a cross sectional approach. The population is 50 young women. This study uses 44 respondents as a sample using the simple random sampling technique in SMK dr. Soebandi. The results showed maladaptive emotional levels (68.2%) and abnormal menstrual cycles (68.2%). Test data analysis using Chi Square with p-value 0.004 < (0.05) which means that there is a relationship between emotional levels and the menstrual cycle in adolescent girls. It is recommended to add information and insight to the public about the relationship between emotional levels and the menstrual cycle.